Etika Kewirausahaan Berbasis Prophetic Intelligence - Rahmat Lutfi Guefara (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Sufism should not be interpreted as an activity solely focused on withdrawing from the world. Instead, Sufism should be utilized as a motivation for every Muslim to seek worldly wealth. However, this worldly wealth should ultimately be used to accumulate good deeds for the hereafter. Prophetic Intelligence is a Sufi study that can be used to integrate the interests of both the worldly and the hereafter. The practice of Sufism in Prophetic Intelligence refers to the example set by the Prophet Muhammad (PBUH). On one hand, he was the Messenger of Allah carrying out duties for the hereafter, and on the other hand, he was a merchant demonstrating how to be a successful entrepreneur in the world. The example of the Prophet Muhammad (PBUH) serves as a model of entrepreneurial ethics.